AGRONOMIC RESPONSE OF INBRED AND HYBRID RICE (ORYZA SATIVA L.) VARIETIES TO METHODS OF SEEDING PREPARATION FOR TRANSPLANTING - Bagarinao, Jay-ar P; Valida, Gelyn D; Coral, Roger N; Cagasan, Ulysses A (Journal of Agriculture and Technology Management; Vol 24 No 2 (2021): Vol 24 No 2 (2021): Journal of Agriculture and Technology Management (JATM) Volume 24 July - December 2021 Issue, 2021)
The method of seedling preparation for transplanted rice is one of the most critical factors of producing healthy and vigorous growth of lowland rice seedlings. This study aimed to determine the growth, yield performance, and profitability of lowland rice hybrid and inbred varieties grown under different methods of seedling preparations for transplanting. The experiment was laid out in a Split-plot RCB design with three replications. The seedling preparations (conventional uprooting and laplap method) were designated as the main-plot while lowland rice varieties (hybrid and inbred rice varieties) as the subplot. The study revealed that uprooting management had no significant effects on plant height (cm), harvest index, herbage yield (tha -1 ), and grain yield (tha -1 ) in rice varieties. Inbred rice varieties produce a greater number of productive tillers hill -1 compared to hybrid rice regardless of seedling preparations (uprooting and laplap methods). However, hybrid rice varieties produced longer panicles and more filled grains than inbred varieties regardless of the methods of seedling preparations. As a result, hybrid rice produced a higher grain yield (tha -1 ) compared to inbreed variety. This resulted in a higher net income of hybrid rice (PhP 57,090.72) than inbred rice, with PhP 54,530.72. The laplap method has a lower production cost than the conventional uprooting method. Hence, laplap method produced higher net income than conventional.